PENGARUH MODEL PEMBELAJARAN KOOPERATIF KARTU ARISAN TERHADAP HASIL BELAJAR PKn SISWA KELAS VII SMP NEGERI 1 KAMPAR TIMUR KABUPATEN KAMPAR - Gusnita, Irny; Eddison, Ahmad; Erlinda, Sri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This study was motivated by the low learning outcomes of students of SMP Negeri 1 East Kampar Kampar District in following civics lesson. The purpose of this study was to determine the effect of cooperative learning model arisan card on learning outcomes in Civics class VII SMP Negeri 1 East Kampar Kampar District. The study population was all students of class VII SMP Negeri 1 East Kampar Kampar District which consists of eight classes with a number of 216 students. The study sample consisted of VII4 class with 27 students and class number VII5 the number of 27 students, thus totaling 54 students. This sample was taken by purposive sampling technique with homogeneity test. Data were collected through observation, documentation, literature study and observation sheet. The results show student learning outcomes in experimental class (VII4) increased compared to the control class (VII5), before the average treated experimental class learning outcomes (VII4) are 50.37 and 87.22 after treatment. While the control class (VII5) average yield of 54.26 while the study before treatment after treatment the average results of their study, namely 69.44. When viewed from the statistical analysis by t test then obtained t 7.29, then tcount compared with the value ttabel with significance level (Î±) 5% = 0.05 df = n1 + n2 - 2 = value ttable is 1.69. Thus that there signifikam influence on a significant level of 5%. Based on the analysis above, there is influence learning outcomes Civics class experimental and control classes due to the use of the learning model koopertaif gathering cardsKey words : cooperative learning model arisan card, student learning out comes, civics